Direct Charge Trapping Multilevel Memory with Graphdiyne/MoS2 Van der Waals Heterostructure. Issue 21 (9th September 2021) - Wen, Jialing; Tang, Wenhui; Kang, Zhuo; Liao, Qingliang; Hong, Mengyu; Du, Junli; Zhang, Xiankun; Yu, Huihui; Si, Haonan; Zhang, Zheng; Zhang, Yue
Abstract: Direct charge trapping memory, a new concept memory without any dielectric, has begun to attract attention. However, such memory is still at the incipient stage, of which the charge‐trapping capability depends on localized electronic states that originated from the limited surface functional groups. To further advance such memory, a material with rich hybrid states is highly desired. Here, a van der Waals heterostructure design is proposed utilizing the 2D graphdiyne (GDY) which possesses abundant hybrid states with different chemical groups. In order to form the desirable van der Waals coupling, the plasma etching method is used to rapidly achieve the ultrathin 2D GDY with smooth surface for the first time. With the plasma‐treated 2D GDY as charge‐trapping layer, a direct charge‐trapping memory based on GDY/MoS2 is constructed. This bilayer memory is featured with large memory window (90 V) and high degree of modulation (on/off ratio around 8 × 10 7 ). Two operating mode can be achieved and data storage capability of 9 and 10 current levels can be obtained, respectively, in electronic and opto‐electronic mode. This GDY/MoS2 memory introduces a novel application of GDY as rich states charge‐trapping center and offers a new strategy of realizing high performance dielectric‐free electronics, such as optical memories and artificial synaptic. Abstract : A graphdiyne (GDY)/MoS2 bilayer memory without any blocking layer is constructed. Through controllable oxygen plasma treatment, relatively large‐area and smooth 2D GDY with additionally introduced CO and C═O is obtained, which enables excellent van der Waals coupling with MoS2 and allows for constructing the bilayer memory. With more introduced states, multilevel and dual operating mode is achieved.